Taxation and tax obligations of restaurants: The portuguese case study - Aldeia, Susana (2019)
The main goal of this paper is to understand the taxation and tax obligations of Portuguese restaurants. For this purpose the Portuguese tax law was investigated, mainly the Corporate Income Tax Law, the Value-Added Tax Law, and the Social Security law. Other important legal dispositions that determine specific tax requirements to this kind of business were also analyzed. The results show that, for medium and big companies, the income taxation is determined having as underlying the accounting profit. This result is adjusted to the tax purposes and for this reason it may be subjected to corrections. In the case of small businesses this determination is simpler. It has as base the total amount of sales and it is presumed as a net income what is applied to the tax rate. The companies need to respect the rules of VAT. It implies to send a tax declaration and to pay or to return tax periodically. Also, restaurants have to assume big tax obligations to be allowed to develop their activity in Portugal. Companies are being overwhelmed with tax compliance obligations. This implies the increase of the companies' context costs and it raises the risk of penalties. Many SMEs have restricted resources and cannot afford to bear these administration expenses. This situation implies the increase of undeclared economy, in which businesses do not pay the correct tax and do not observe the tax obligations, supporting therefore less costs to develop their activity.